To solve the system of equations:
1) Rearrange the first equation in terms of x:
6x + 3y = 9
6x = 9 - 3y
x = (9 - 3y)/6
x = (3 - y)/2
2) Substitute the value of x in the second equation:
2x + 3y = 1
2((3 - y)/2) + 3y = 1
3 - y + 3y = 1
(2y + 3) = 1
2y = 1 - 3
2y = -2
y = -2/2
y = -1
3) Substitute the value of y into the first equation to find x:
x = (3 - y)/2
x = (3 - (-1))/2
x = (3 + 1)/2
x = 4/2
x = 2
The solution to the system of equations is x = 2 and y = -1.
6x + 3y = 9
2x + 3y = 1
1 answer